Incidence of radiation necrosis following different radiotherapy fractionation schedules for intracranial meningiomas - Palička, M; de Jong, A M; David, S; Rybář, M; Jackaninová, J; Knybel, L; Reguli, Š; Blažek, T; Tomoszková, S; Verhoeff, J J C; Cvek, J (Strahlentherapie und Onkologie, 2025)
BACKGROUND AND PURPOSE: Radiotherapy (RT) may be a safe alternative to surgery for selected intracranial meningiomas, particularly in eloquent or high-risk surgical locations. Reported studies of stereotactic RT have utilized stereotactic radiosurgery (SRS), fractionated stereotactic radiotherapy (hFSRT), or conventional radiotherapy. This retrospective study aimed to compare toxicity in a large international cohort. MATERIALS AND METHODS: A total of 473 consecutive patients were treated for intracranial meningioma at two radiation oncology clinics. The patients underwent various treatment modalities, including stereotactic radiosurgery (SRS), hypofractionated stereotactic radiotherapy (hFSRT, 2-5 fractions), or normofractionated stereotactic radiotherapy (nFSRT, 28-30 fractions) using CT-linac or Cyberknife radiation techniques. The evaluation of potential brain edema and radiation necrosis (RN) was conducted using magnetic resonance imaging (MRI). RESULTS: Radiation-induced brain edema occurred in 11.0% of patients, including 4.9% with symptomatic edema requiring corticosteroid therapy, and 4.0% of patients developed radiation necrosis. Despite a smaller irradiated tumor volume, the risk of radiation-related toxicity was higher with SRS compared to hFSRT and nFSRT, for both brain edema (hazard ratio [HR] = 4.10, 95% confidence interval (CI; 2.02; 8.26), p < 0.001) and RN (HR = 11.07, 95% CI (2.65; 46.24), p < 0.001). Cox regression showed a 33 and 28% increased risk of brain edema and RN per 1 cm3 of tumor volume (HR = 1.33, 95% CI (1.21; 1.46), p < 0.001 and HR = 1.28, 95% CI (1.13; 1.46), p < 0.001). For tumor volumes above the median (2.05 cm3), the risk of toxicity following SRS was significantly higher for edema (HR = 9.70, 95% CI (2.90; 32.40), p < 0.001) and RN (HR = 13.34, 95% CI (1.73; 102.80), p = 0.013). CONCLUSION: Stereotactic radiotherapy and radiosurgery are safe treatment options for intracranial meningiomas. However, our data indicate a significantly increased risk of radiation necrosis and edema after SRS for tumors larger than 2 cm3 (diameter > 1.55 cm). This study also highlights the safety of both nFSRT and hFSRT in the treatment of larger tumors, supporting treatment selection based on tumor volume.
Keywords: Radionecrosis; Radiosurgery; Cyberknife; Brain tumor; Meningioma; Radiation necrosis